Nanoscale Morphology of PTB7 Based Organic Photovoltaics as a Function of Fullerene Size - Roehling, John D.; Baran, Derya; Sit, Joseph; Kassar, Thaer; Ameri, Tayebeh; Unruh, Tobias; Brabec, Christoph; Moule, Adam J. (Scientific Reports, 2016)
High efficiency polymer:fullerene photovoltaic device layers self-assemble with hierarchical features from ångströms to 100's of nanometers. The feature size, shape, composition, orientation, and order all contribute to device efficiency and are simultaneously difficult to study due to poor contrast between carbon based materials. This study seeks to increase device efficiency and simplify morphology measurements by replacing the typical fullerene acceptor with endohedral fullerene LuN@PC BEH. The metal atoms give excellent scattering contrast for electron beam and X-ray experiments. Additionally, LuN@PC BEH has a lower electron affinity than standard fullerenes, which can raise the open circuit voltage of photovoltaic devices. Electron microscopy techniques are used to produce a detailed account of morphology evolution in mixtures of Lu 3 N@PC 80 BEH with the record breaking donor polymer, PTB7 and coated using solvent mixtures. We demonstrate that common solvent additives like 1,8-diiodooctane or chloronapthalene do not improve the morphology of endohedral fullerene devices as expected. The poor device performance is attributed to the lack of mutual miscibility between this particular polymer:fullerene combination and to co-crystallization of Lu 3 N@PC 80 BEH with 1,8-diiodooctane. This negative result explains why solvent additives mixtures are not necessarily a morphology cure-all.